Examining Factors that MA Students face while conducting their Theses: The Case of School of Education and behavioral Sciences, Wolaita Sodo University. - Labiso , Tafano Ouke (Advances in Social Sciences Research Journal, 2019)
The purpose of this study was to dig out the root causes for the challenges that MA/or second degree students face while conducting the research(Theses). Hence, to realize and achieve this purpose, qualitative case study research method and design respectively were employed. Both primary sources and secondary sources were employed. The primary sources were 40 regular and summer MA students, and the secondary sources were the Theses materials of 4 years. Simple random sampling technique was used to select 40 Theses materials out of the 4 year batches. Observation and document analysis were made to collect data. Data were analyzed qualitatively through narration. The findings showed that there was the knowledge gap on the part of the researchers about the fundamentals of research on one hand and on the other hand the concerned bodies gave little attention for capacitating the researchers, and also gave low attention for monitoring the progress of the researchers while conducting research. And it could be concluded that there were a lot of activities that the concerned bodies like school of graduate studies, heads and deans of the departments and schools or colleges, academic vice presidents, and even instructors have to do to capacitate the researchers or MA students. Therefore, it was suggested that statistical courses should be integrated with research courses and also there should be the content regarding advanced analysis of the findings, and also the training for the students should be strengthened and also there should be monitoring and evaluation system developed.